Symbolismus im Spannungsfeld zwischen aesthetischer und eschatologischer Existenz Motivische Semantik im lyrischen Werk von Otokar Březina - Vojvodík, Josef (Slavistische Beitraege, 1998)
The main subject and aim of the present work is the exploration of the motivic semantics of the lyrical work of Otokar Březina in its evolutionary dynamics with special reference to the mythopoetic aspects of the aesthetic constitution of meaning.